2022
DOI: 10.3389/fvets.2022.1034610
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiological analysis of mcr-1-harboring Escherichia coli collected from livestock settings in Vietnam

Abstract: Livestock has been implicated as a reservoir for antimicrobial resistance (AMR) genes that can spread to humans when antimicrobials are used in animals for food production to treat clinical diseases and prevent and control common disease events. In Vietnam, mcr-1-harboring Escherichia coli (MCRPEC) strains have been isolated from humans, animals (chickens, pigs, and dogs) feces, flies, foods, and the environment (rainwater, well water, and irrigation water) in communities and from clinical specimens in hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The high incidence of mcr in our study is in accordance with a previous report ( Dadashi et al, 2022 ), consistent with its identification as the globally predominant colistin-resistance gene. At present, mcr -1 could confer colistin resistance with broad minimal inhibitory concentrations (MICs) of 2–16 mg/L ( Nang et al, 2019 ), for instance, 74% of mcr -1 positive E. coli isolates had MICs at 2 mg/L ( Nguyen et al, 2022 ), while 52% of mcr -1 positive E. coli isolates in another study exhibited MICs of 4∼8 mg/L ( Ćwiek et al, 2021 ). For other mcr genes, mcr -3 has been globally disseminated since it was first reported in Yin et al (2017) , and this gene inside the linker has been found to appear as a facilitator of colistin resistance ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of mcr in our study is in accordance with a previous report ( Dadashi et al, 2022 ), consistent with its identification as the globally predominant colistin-resistance gene. At present, mcr -1 could confer colistin resistance with broad minimal inhibitory concentrations (MICs) of 2–16 mg/L ( Nang et al, 2019 ), for instance, 74% of mcr -1 positive E. coli isolates had MICs at 2 mg/L ( Nguyen et al, 2022 ), while 52% of mcr -1 positive E. coli isolates in another study exhibited MICs of 4∼8 mg/L ( Ćwiek et al, 2021 ). For other mcr genes, mcr -3 has been globally disseminated since it was first reported in Yin et al (2017) , and this gene inside the linker has been found to appear as a facilitator of colistin resistance ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of multidrug-resistant (MDR) E. coli has been observed in Asia [49][50][51][52][53][54], Africa [55][56][57][58], and four European countries [59], with varied rates and resistance to more than four types of medicines. Further research is required to understand the transmission mechanism of MDR E. coli within agricultural contexts and the risk variables that affect temporal changes.…”
Section: Worldwide Prevalence Of Esbl E Coli In Livestockmentioning
confidence: 99%
“…Due to the high prevalence of colistin-resistant E . coli carrying mcr in livestock as well as the possibility of horizontal transfer among various hosts, there is a high risk of the spread of resistant bacteria in the human community, given that animals are used for food production [ 17 ]. Such a spread among communities and regions may be influenced by the people’s lifestyles, which may also affect colistin-resistant bacteria epidemic patterns.…”
Section: Introductionmentioning
confidence: 99%